Antioxidant activity, color chromaticity coordinates, and chemical characterization of monofloral honeys from Morocco. Issue 9 (2nd September 2017) - Petretto, Giacomo Luigi; Tuberoso, Carlo Ignazio Giovanni; Fenu, Maurizio Antonio; Rourke, Jonathan P.; Belhaj, Omar; Pintore, Giorgio
ABSTRACT: The bioprospecting of several monofloral Moroccan honeys was carried out. The antiradical activity expressed as mmol Trolox equivalents/kg of honey and evaluated by 2, 2-diphenyl-1-picrylhydrazyl assay, ranged from 0.15 for euphorb honey to 1.08 for citrus honey. The antioxidant activity expressed as mmol Fe 2+ /kg and evaluated by ferric ion reducing antioxidant power assay, ranged from 0.96 for euphorb honey to 4.74 for orange honey. The total phenol content was evaluated by colorimetric assay, while the color attributes were evaluated as transmittance data. Significant Pearson correlation factors were found between total polyphenol amount and antioxidant activity and between color attributes and antioxidant activity. Furthermore the chemical composition of volatile organic compounds was determined. The volatile organic compounds chemical composition of the studied honeys was mainly represented by terpene and benzene derivatives, Maillard reaction products, isoprenoids, and hydrocarbons. The volatiles fingerprint, as well as a targeted high-performance liquid chromatography analysis of the polar components, was used to tentatively confirm the declared botanical origin of the samples studied.